Personal und Arbeit : Einführung in das Personalmanagement. - Oechsler, Walter A. (De Gruyter Studium., 2015)
<!Doctype html public ""-//w3c//dtd html 4.0 transitional//en""> This textbook is written from an action-oriented perspective. It not only presents the theoretical and methodological principles of putting personnel policy tools into practice but also covers their function and impact on the work process.